Antimalarial cytoskeletal targeting with broad apicomplexan activity - Darshan V. Trivedi; Anastasia Karabina; Tiantian Jiang; Daisy Chen; Nimisha Mittal; Tonnie Huijs; Rianne van der Laak; Jin H. Jeon; Tomas Yeo; Dihia Moussaoui; James P. Robblee; Marianna Akey; et al. (Proceedings of the National Academy of Sciences, 2026)
Malaria is a devastating disease that resulted in an estimated 610,000 deaths in 2024, the majority being children under the age of five. Here, we use KNX-115 to illustrate multistage antiparasitic activity upon targeting the cytoskeletal enzyme Plasmodium falciparum myosin A (PfMyoA). KNX-115 inhibits purified actin-activated ATPase with a potency in the low nanomolar range and >50-fold selectivity against cardiac, skeletal, and smooth muscle myosins. KNX-115 traps PfMyoA in a state that binds weakly to actin. A 2.35 Å resolution structure of KNX-115 bound to PfMyoA reveals critical interactions contributing to its mechanism of action. Importantly, in vitro evolution data reveal that KNX-115 engages PfMyoA as a sole cellular target. Inhibiting PfMyoA blocks the development of the blood and liver stages of laboratory strains of P. falciparum , with no liver cell toxicity, sporozoite cell traversal and motility, and sporozoite development in the mosquito. Inhibiting PfMyoA completely kills parasites after 96 h of treatment. Furthermore, KNX-115 is equally effective at inhibiting a panel of Plasmodium strains resistant to experimental and marketed antimalarials and shows inhibitory activity against P. falciparum circulating isolates from the Brazilian Amazon. Inhibiting PfMyoA with KNX-115 also blocks the blood stage of a laboratory strain of Plasmodium vivax . In line with the evolutionary identity of MyoA among various apicomplexan parasites, KNX-115 also inhibits Cryptosporidium and Eimeria MyoA in vitro and is an effective inhibitor of Cryptosporidium , Toxoplasma, and Eimeria cellular growth, with EC 50 s similar to those found for blood and liver stage Plasmodium .